DIRECTIONS OF INCREASING THE INNOVATION CAPACITY OF INDUSTRIAL ENTERPRISES (World Economics and Finance Bulletin, 2023)
In this article, the classification of factors influencing the innovation potential of industrial enterprises andcomponents of innovation potential, advantages of innovation cluster organization and evaluation methods are presented.The sequence of evaluation of innovative potential in industrial enterprises, the system of measures to stimulate innovative activity is presented
Keywords: Innovation; innovation approach; assessment methods